2012
DOI: 10.1158/1078-0432.ccr-11-2994
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Use Is Associated with Better Survival of Diabetic Patients with Pancreatic Cancer

Abstract: Purpose Accumulating evidence suggests that metformin has antitumor activity. The aim of this study was to determine whether metformin use has a survival benefit in patients with pancreatic cancer. Experimental Design We conducted a retrospective study of diabetic patients with pancreatic cancer treated at MD Anderson Cancer Center. Information on diabetes history including treatment modalities and clinical outcome of pancreatic cancer was collected using personal interviews and medical record review. Surviv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
216
3
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(235 citation statements)
references
References 42 publications
10
216
3
6
Order By: Relevance
“…Recent studies report that diabetic cancer patients who take metformin exhibit improved outcomes as compared with patients taking other antidiabetic drugs (10), and this has spurred interest in possible clinical applications of metformin for cancer therapy. One of the hallmarks of metformin action is associated with inhibition of the mTOR signaling in both cancer and non-cancer tissues and cells (15)(16)(17)(18)(19)(20)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies report that diabetic cancer patients who take metformin exhibit improved outcomes as compared with patients taking other antidiabetic drugs (10), and this has spurred interest in possible clinical applications of metformin for cancer therapy. One of the hallmarks of metformin action is associated with inhibition of the mTOR signaling in both cancer and non-cancer tissues and cells (15)(16)(17)(18)(19)(20)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…A comparable study in pancreatic cancer patients showed that diabetics using metformin had a 32% lower risk of death and longer overall survival than diabetics using other drugs (10). This latter study recommended using metformin as a supplemental therapy for treatment of pancreatic cancer patients (10).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Some pharmacoepidemiologic studies have suggested that metformin may have antineoplastic activity (21)(22)(23)(24)(25)(26)(27) but others have not supported this view (28)(29)(30)(31). Similarly, some (10) but not all (32) laboratory studies suggest that metformin has antineoplastic activity.…”
Section: Introductionmentioning
confidence: 99%